Menganalisis Keberhasilan Provinsi Kepulauan Riau Pasca Pemekaran Daerah di Bidang Ekonomi dan Infrastruktur (International Forum of Researchers and Lecturers, 2025)
This study analyzes the success of the Riau Islands Province post-regional expansion in the fields of economy and infrastructure. The territorial expansion carried out in 2002 aimed to enhance government efficiency and accelerate regional development. Despite notable progress, such as economic growth exceeding the national average and controlled inflation, significant challenges remain, including dependency on transfers from the central government. The Fiscal Independence Index (IKF) indicates that most districts and cities in Riau Islands Province are still categorized as